Green Manufacturing Practices for Improving Sustainability Performance in Packaging Manufacturing MSMEs - Hasibuan, Sawarni; Kandasamy, J; Purba, H Hardi; Jaqin, C (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
To achieve efficient and environmentally sustainable manufacturing, it is necessary to identify lean and green wastes inherent in processes, analyze their causes, and formulate and implement a strategy for waste elimination. This community service activity aims to systematically disseminate how to integrate lean and green paradigms to increase operational efficiency while reducing the environmental impact of packaging Small, Micro, and Medium Enterprises (MSMEs) in Bekasi. Training on applying the green value flow mapping process provides a systematic approach to identifying green wastes using lean tools such as VSM and RCA, in a real case, and packaging manufacturing MSMEs. Participants will be encouraged to learn how to simplify the creation of green value flow mapping and integrate it with traditional VSM to get a novel Green-Integrated VSM (GIVSM) to visualize lean and green waste in value streams. As an activity partner is Vellore Institute of Technology (VIT), India. The outcome of this activity will be published in online media and journals. Implementation of community service activities through self-assessments, presentations, discussions, consultations, and guidance in developing partner research and roadmaps. Contribution to Sustainable Development Goals (SDGs):SDG 12: Sustainable Production & ConsumptionSDG 9: Industrial Innovation & Responsible ProductionSDG 13: Climate ActionSDG 17: Partnership for Sustainability